Regulation, control and oversight of the financial market in terms of innovative development - Daribayeva, M. Zh. (Journal of Economic Research & Business Administration, 2016)
The article examines the role of the state in the management of financial resources, as well as the role of government in the formation of budget revenues on the basis of sound regulations, management, regulation and oversight of the financial market of the Republic of Kazakhstan. Regulation and oversight of the financial market is very important to maintain a balance in the financial and economic situation of the country. Government regulation and oversight of financial market and financial organizations need to maintain stability in the financial system of the Republic of Kazakhstan, including in support of consumer financial resource and provide their legal protection. In this regard, the article examines the major problems in the financial markets, solutions and provide recommendations to improve the financial market of the Republic of Kazakhstan.